O ważeniu danych przy brakach odpowiedzi z wykorzystaniem metod nieparametrycznych - Gamrot, Wojciech (On weighting adjustments for nonresponse using nonparametric methods, 2007)
The occurrence of nonresponse in a sample survey usually introduces the bias in population parameter estimates and reduces their precision. Several estimation methods have been developed to compensate for these effects. One of the procedures broadly discussed in the literature is the twophase sampling for nonresponse which is based on subsampling initial nonrespondents and recontacting them. Another popular method known as weighting adjustment relies on constructing the estimator using weights dependent on individual response probabilities which are known in advance or estimated. In this paper an attempt is made to construct another mean value estimator by combining these two approaches, and assuming that individual response probabilities are estimated using nonparametric methods. The results of simulation experiments assessing its properties are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 83-91